Four Phases Quality Function Deployment (QFD) By Considering Kano Concept, Time And Manufacturing Cost - Moses L. Singgih; Dyah L. Trenggonowati; Putu D. Karningsih (International Conference on Engineering and Technology Development (ICETD), 2013)
Each company must carry out product development to maintain or build sales. Relationship between specifications and parameters of quality products to the wishes of the customer is an important consideration in doing product development. Product development methods QFD (Quality Function Deployment) has been widely applied in industry to maximize customer satisfaction based on quality, cost, time and other, become source of constraints. Quality, time and cost are important factors for a company to maintain existency of the company in the industry. This study will provide customer deployment requirements to consider not only the quality factors are more often a point of view assuming the successful development of a product, but also on the factors of time and cost. Factors to be considered in stages creating new products or improving old products are not only detailed data about the four phases of phasing as product planning, product design, process planning, process control and planning is needed, but also a complete view of the overall technical response . The final integration of the four phases of QFD is influential in producing and marketing the products. Team of product development must plan how to design new products to exploit existing technical response. Matters relating to the quality characteristic and the voice of stakeholders is very relevant and should be well understood and thoroughly. Technical approach to a more detailed response can lead a team of product developers to pay attention to the changes of each phase to obtain the allocation of resources for each of the responses are perfectly.